Respiratory and functional physiotherapy techniques in the health of HIV-positive men - Chinelatto, Vinicius Alves (Revista Coleta Científica, 2025)
Research highlights that HIV infection is associated with a greater vulnerability to physical frailty, including respiratory and functional impairment. Studies show that antiretroviral therapy can mitigate some of these adverse effects, but challenges remain in maintaining the overall health and functionality of these patients. Respiratory physiotherapy encompasses a variety of techniques, such as breathing exercises and lung expansion, which aim to improve lung function and reduce respiratory complications such as pneumonia and opportunistic infections. Meanwhile, functional physiotherapy focuses on physical rehabilitation, with specific exercises to improve muscle strength and functional capacity. Both approaches are essential to minimizing the impact of HIV on physical health and promoting independence and quality of life. The study also emphasizes the importance of patient education and psychosocial support as essential components of treatment. Promoting healthy lifestyle habits, such as regular exercise and smoking cessation, is crucial to improving long-term outcomes. Finally, this document highlights the need for more research and interventions focused on physical therapy for HIV-positive men, with the goal of developing more effective and personalized treatment protocols tailored to the individual needs of these patients.